PROGRAM PENANAMAN SAYURAN BAGI WARGA RT 37 MALANGAN, KOTA YOGYAKARTA SEBAGAI UPAYA PENGHIJAUAN DAN MENDUKUNG EKONOMI - Rokhana Dwi Bekti; Kris Suryowati; Hadi Prasetyo Suseno (IKIP SILIWANGI, 2020)
The problem of environmental pollution still often occurs in urban areas. One of them is in RT 37 / RW 13 Malangan, Giwangan, Umbulharjo District, Yogyakarta City, DIY. The team chose this partner on the grounds that the partner needed treatment to reduce air pollution, because the location is close to Giwangan Terminal and South Ring Road which is full of transportation. In addition, the community needs an economic strategy for how to meet the daily needs of Covid-19. The solution offered is a vegetable planting program for residents so that they can independently meet their daily needs and become one of the greening steps to reduce air pollution. The methods of implementation carried out include planning activities, program socialization, training and provision of vegetable seedlings, to program evaluation. This activity went well, the partner community gave a positive response and got many benefits. The community has planted vegetables in their homes so that the environment becomes beautiful, comfortable, beautiful, and the community can meet the daily needs of the vegetables.